Efeito de vernizes fluoretados suplementados com trimetafosfato de sódio na desmineralização e remineralização do esmalte bovino: estudos in vitro e in situ - Manarelli, Michele Mauricio [UNESP] (2014)
The aim of the study was to assess the effects of fluoridated varnishes supplemented with sodium trimetaphosphate (TMP) on enamel demineralization and remineralization. For this purpose, the study was divided into 4 chapters. First, the amount of fluoride (F) and phosphate (P) released in artificial saliva solutions (24 h) were measured after the application of varnishes containing 2.5% NaF, 5% NaF, 5% TMP, 2.5% NaF/5% TMP, 5% NaF/5% TMP, besides a PLACEBO formulation (no NaF or TMP) and a commercial formulation (Duraphat), as described in Chapter 1. The effects of these varnishes on the remineralization of caries-like lesions, as well as on the demineralization of sound enamel were assessed on Chapters 2 and 3, respectively, using pH-cycling models. Finally, the remineralizing effect of PLACEBO, 5% NaF and 5% NaF/5% TMP was evaluated using and in situ protocol (Chapter 4). Specimens were analyzed by surface hardness (SH), percentage of SH recovery (%SHR), cross-sectional hardness (ΔKHN), polarized light microscopy, as well as firmly and loosely (CaF2) bound fluoride. A dose-response relationship was observed between NaF and TMP concentrations in the formulations and the amount of F and P released into artificial saliva. Although a partial inhibitory effect on F and P release was observed in the presence of the two salts, a synergistic effect was observed in %SHR and ΔKHN on the remineralization of caries-like lesions, as well as on the reduction of sound enamel demineralization (SH e ΔKHN) for varnishes containing NaF e TMP. Under both conditions, the protective effect of the 5% NaF/5% TMP varnish was significantly higher than the other groups in vitro. The same pattern was confirmed in situ on the remineralization carious enamel. Firmly and loosely bound fluoride were contradictorily lower for varnishes containing TMP when...